Pisa and the evaluation. Mirror or food -side notes- - Fernández Mayo, Ramiro (Avances en Supervisión Educativa, 2010)
From the 23rd to the 26th of November, it took place in La Palma the International Symposium PISA under Examination -a change in knowledge, a change in tests and a change in schools-. The author, who took part in the symposium, describes and extracts conclusions from the long and fruitful talks among the most credited specialists who came from all over the world and attended the symposium by courtesy of CESE -Comparative Education Society in Europe- and its Chairman, Mr Miguel A. Pereyra, a La Palma native-born citizen.